Mabedda Bola ritual in South Sulawesi; The relationship between handprints in traditional house and hand stencils in prehistoric caves - Permana, R. Cecep Eka; Pojoh, Ingrid H.E.; Arifin, Karina (Wacana, Journal of the Humanities of Indonesia, 2017)
Mabedda Bola is a ritual which has been handed down from the ancestors of the Bugis - Makassarese people in South Sulawesi. At the ceremony which is called menre bola baru, held as part of the ritual inauguration of a new house, the Mabedda Bola, handprints are made on the poles and walls of the new house. In the region in which this custom is still honoured, hand stencils on the walls of the prehistoric caves have also been found. This article examines the significance of handprints in the Mabedda Bola ritual which might possibly be related to the hand stencils on the walls of the prehistoric caves. Using the perspective of analogy, one of the methods of ethnoarchaeology, it has been discovered that handprints and hand stencils take more or less the same form. The similarities between them hint at the same behavioural patterns between the present day and the prehistoric period. The print of the hand palm is meant to mark the ownership of the family or group who dwell in a traditional house or it is thought in a particular cave. Moreover, it is and was to avert danger or the intrusion of bad influences from outside.